Local piezoelectric properties of perforated ferroelectric barium–strontium titanate films - N. E. Sherstyuk (Российский технологический журнал)
Objectives. Focused ion beam etching remains one of the most common methods for fabricating 2D photonic crystals and structures based on functional materials. This technique is quite well developed for semiconductors. But at the same time, the change in the properties of ferroelectric materials under the action of a focused ion beam, including parameters of distribution and switching of the polarization state under the action of an electric field, remains poorly studied. The purpose of this work is to determine the local piezoelectric parameters in perforated ferroelectric films of barium strontium titanate (Ba0.8Sr0.2TiO3) with ordered vertical air channels fabricated by focused ion beam etching.Methods. Experimental studies were conducted using piezoresponse force microscopy under applied electric field in planar geometry.Results. It is shown that the perforation of a ferroelectric film leads not only to the formation of significant inhomogeneities in the piezoelectric response distribution in the structure, but also to the noticeable increase in the magnitude of both the vertical and lateral components of the piezoresponse near the perforation holes. The calculation results showed that the greatest enhancement is observed for the lateral component of the piezoresponse: from 5 pm/V for a nonperforated film to 65 pm/V in the perforated area.Conclusions. The most probable mechanism for such a change in properties is the influence of a disturbed layer that occurs at the boundary and the inner surface of vertical air channels. The properties of this layer are due to two factors: amorphization of the structure as a result of the focused ion beam etching and the appearance of pinned domain states near the hole, leading to the formation of the complex piezoresponse distribution both at the hole boundary and in the gap between the perforations. The information obtained is important for understanding the peculiarities of the formation of local piezoelectric and ferroelectric responses in photonic crystals fabricated by focused ion beam etching, as well as for finding ways to control their state when an external electric field is applied.